Rehabilitation and Return to Sport Testing After Anterior Cruciate Ligament Reconstruction: Where Are We in 2022? - Alli Gokeler, Ph.D., P.T; Bart Dingenen, Ph.D., P.T; Timothy E. Hewett, Ph.D (Elsevier, 2022)
Abstract: Athletes who sustain an anterior cruciate ligament (ACL) injury often opt for an ACL reconstruction (ACLR) with the goal and expectation to return to sports at the preinjury level. The proportion of athletes who successfully return to preinjury-level sport is low and disappointing, whereas the rate of second ACL injury in athletes under the age of 20 has been reported to be as high as 40% after return to sport (RTS). Although in recent years, new insights pertaining to RTS have been published, the lack of validity of RTS criteria after ACLR remain. The purpose of this clinical commentary is to present a critical overview of the current literature on RTS testing after ACLR.